Might we be Calling Problems Seen in Autism Spectrum Conditions: ‘Poor Theory of Mind,’ when Actually they are Related to Non-Generalised ‘Object Permanence’? - Lawson, Wenn B.; Dombroski, Brynn A. (Journal of Intellectual Disability - Diagnosis and Treatment, 2015)
Autism spectrum conditions (ASC) and the delayed development of object permanence is often not questioned, and is rarely understood. The following paper attempts to explore this idea and suggests reasons for why such development is delayed and the possibility that certain difficult behaviours seen in children with ASC are less likely to be connected to having poor theory of mind and more connected to lacking generalized concepts of object permanence.